Longitudinal development of physical, perceptual-cognitive and skill predictors of talent in academy and professional female football players - Beavan, A.; Spielmann, J.; Altmann, S.; Härtel, S. (Journal of Sports Sciences, 2024)
Existing literature on talent development predominantly focuses on male athletes, with limited representation of female athletes. This study aims to address this gap by examining the long-term development of female football players in an elite club. Routine lab-based assessments were conducted on 238 athletes across six teams for 7 years to determine how physical, perceptual-cognitive, and skill performance predictors fluctuated with player age and developmental stage (sampling 9-11y, specializing 12-14y, investment 15-18y, and performance +18y). The developmental stage was a significant predictor of improved performance for each talent indicator (p < .001), with each consecutive stage significantly outperforming the previous stage in all domains with moderate to large effect sizes (0.07-0.40 np2). Improvement rate was higher in young adolescence (<15) and slower approaching adulthood (>18y). Playing position influenced performance scores on several physical and technical skill predictors (p = .001), but not perceptual-cognitive ones (p = .11). Players progressed continuously from the sampling to the performance stage, contradicting previously reported plateaus observed when athletes reached the investment stage. Benchmark data are provided across age and playing position to better understand what is required for successful participation at an elite level at varying age groups in female soccer.